INTELTRADE: Intelligent Peer-to-Peer Energy Trading System With Dynamic Pricing and Coalition Formation - Nicholas Kemp; Md Sadman Siraj; Eirini Eleni Tsiropoulou; Symeon Papavassiliou (IEEE Access)
The decentralization of energy generation and consumption has become increasingly vital, with peer-to-peer (P2P) energy trading promoting resilience, and sustainability. This paper introduces INTELTRADE, a system addressing the energy sustainability and pricing challenges in P2P trading. INTELTRADE integrates a sophisticated coalition formation mechanism and an optimal pricing policy. Initially, the Approximate INTELTRADE (AINTELTRADE) mechanism uses matching theory to quickly determine the initial buyer-seller matches by ignoring prosumers’ externalities. This output feeds the Accurate INTELTRADE (AccINTELTRADE) mechanism, which refines the coalition formation using game theory while considering the prosumers’ externalities. Additionally, a non-cooperative game among energy-selling prosumers is formulated, deriving a unique Nash Equilibrium to maximize the sellers’ profits. INTELTRADE’s efficacy and scalability are validated through simulations with real-world data. A detailed comparative evaluation demonstrates INTELTRADE’s superiority in meeting the buyers’ energy demands and optimizing the sellers’ profits.